Participants wearing specially tailored garments - Mumbai Archive Project Team (Jio Institute, 2024)
Participants in the parade wear specially tailored garments, makeup, jewellery, and accessories. The parades are open and inclusive, where people of all ages, genders, religions, and walks of life participate.